Distributional price effects of rent controls in Berlin: When expectation meets reality - Lorenz Thomschke (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2016)
An enormous increase of initial rents in many German cities over the last decade has prompted the current grand coalition to implement a new rent control called "Mietpreisbremse" in 2015 (literally a brake on rental prices). This reform aims to stop exploding rents and to provide particularly more affordable rental housing in the lower and medium rental price segment. Since then, rental prices of re-lettings are capped at a local rental index in declared areas. As an exception, newly built flats or those that have been reconstructed extensively are not affected by the reform and landlords may always uphold the rent paid by previous tenant. I apply a classical difference-in-difference strategy and a new changes-in-changes model including covariates in order to analyze both average and distributional price effects of the intervention in Berlin. The basis for empirical results is data on newly offered rental prices from 2012 to 2016 that is also enhanced with the local rental index and previous rents. Thereby, I can define the range of effects one could reasonably expect beforehand. Results indicate that the reform indeed lowered initial rents temporarily. In contrast to the reforms intention, however, significant effects are found only in the upper price segment. The effects also fall short of anticipated expectation and fade out too fast. Meanwhile, newly offered rental prices even outrun the pre-reform level, which highlights the lack of enforcement supplementary. I will therefore argue that the reform so far has failed to meet the intended objective and is poorly targeted.
Keywords: R21; R23; R31; R33; C1; 330; rent control; quantile regression; counterfactual distribution; difference-in-difference; changes-in-changes